The Change of Forms and the Value of the Dance performance of Barongan Risang Guntur Seto - Guntaris, Endik; Cahyono, Agus; Utomo, Udi (Universitas Negeri Semarang, 2019)
Barongan Risang Guntur Seto dance is one of dances that has experienced a changing of form from spontaneous to organized performance since 2016. The management and the change done by Barongan Risang Guntur Seto artists have altered the simple values of traditional performing art to be a glamorous values or it is called gebyarby Blora people. The purpose of this research is to analyze and to describe the change of form and value of Barongan Risang Guntur Seto dance.Theoretically, this research used qualitative method with interdisciplinary approach of science, they are ethnochoreology and Arts Sociology. The technique of data collection was done by observation, interview and document study. The data validity checking used source triangulation. The data analysis was done by data reduction, data presentation, and conclusion. The results show that the chane of form and value of Barongan Risang Guntur Seto dance performance involves movement, music, property, stage, and lighting. The suggestion for artists of Barongan Risang Guntur Seto dance is to always active in renewing the dance in accordance to the era and to always be consistent in emphasizing the simplicity and family values as an identity of Blora people.